THE ROLE OF SERVANT LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON THE EMPLOYEES - Kusmana, Agus; Pratiwi, Endah Andriani; Setiadi, Iwan Kresna (International Research of Multidisciplinary Analysis, 2023)
The Role of Servant Leadership on Organizational Citizenship Behavior (OCB) on the employees. This causality study between Servant Leadership and Organizational Citizenship Behavior (OCB) was conducted to analyze the role of Servant Leadership to OCB on the employees. This study used a theoretical approach from Greenleaf (1999) with 8 dimensions that proposed by Barbuto (2006), namely the Altruistic calling, the Emotional healing, the Wisdom, the Persuasive mapping, the Organizational stewardship, and the Humility; and theory by Organ(1988) for the OCB. Total sampling technique was used in collecting the research sample of 50 employees of Company X consisted by the employee from IT Department, Operators and the Agency. The measurement tool of Servant Leadership is a standard measuring tool that was adapted into Indonesia version by Seger Handoyo (2010) which consist 38 question items.  The measuring instruments of this research is made by the author, with the validity of measuring instruments of 0.298 to 0.665, and the reliability of α = 0.809 based on Cronbach's.The results showed that the Servant Leadership has the influence on Organizational Citizenship Behavior with an R Square of 0.910 with a high level of Servant Leadership and Organizational Citizenship Behavior